Melatonin Suppresses Microglial Necroptosis by Regulating Deubiquitinating Enzyme A20 After Intracerebral Hemorrhage - Lu, Jianan; Sun, Zeyu; Fang, Yuanjian; Zheng, Jingwei; Xu, Shenbin; Xu, Weilin; Shi, Ligen; Mei, Shuhao; Wu, Haijian; Liang, Feng; Zhang, Jianmin (Frontiers in Immunology, 2019)
Cell death is deeply involved in pathophysiology of brain injury after intracerebral hemorrhage (ICH). Necroptosis, one of the recently discovered forms of cell death, plays an important role in various diseases, including ICH. Previous studies have suggested that a considerable number of neurons undergoes necroptosis after ICH. However, necroptosis of microglia after ICH has not been reported to date. The present study demonstrated for the first time that necroptosis occurred in the microglia surrounding the hematoma after ICH in C57 mice, and melatonin, a hormone that is predominantly synthesized in and secreted from the pineal gland, exerted a neuroprotective effect by suppressing this process. When we further explored the potential underlying mechanism, we found that melatonin inhibits RIP3-mediated necroptosis by regulating the deubiquitinating enzyme A20 (also known as TNFAIP3) expression after ICH. In summary, we have demonstrated the role of microglial necroptosis in the pathogenesis of ICH. More importantly, A20 was identified as a novel target of melatonin, which opens perspectives for future research.